“JANGAN BAKUKAN AKU” IDENTITAS HYBRID ISLAM DI INDONESIA - Darwin Darmawan (Universitas Gadjah Mada, 2012)
This paper is a result of series of interview with Reza and Nina and analyse those interview with hybridity perspective. This perspective is very useful to understand the multidemensional and exible characteristic of identity. Identity cannot be regarded in homogen and stable way of understanding. That awarenes in turn, helps to build respect toward the other, something that is needed in multicultural society.